2021
DOI: 10.32914/i.54.3-4.5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of credibility of influencers recommendations on social media on consumers behavior towards brands

Abstract: Companies are becoming increasingly aware of the importance and opportunities provided by social media in order to communicate faster and more efficiently with their consumers. In order to convey the message about the value of their brands to their target market, organizations hire influential people who are considered to be the creators of public opinion in a virtual environment. Nowadays, social media are crowded with micro and macro influencers, or at least those who present themselves as such. Their main j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…According to the findings of this study, social media influencer marketing plays a significant role in building brand awareness for any organization (β = 0.520, t = 5.150, p < 0.001). This is consistent with previous studies that have also found social media influencer marketing to be an effective way to increase brand awareness (Kwiatek et al, 2021). However, Vrontis et al…”
Section: H3: Social Media Influencer Marketing Has a Positive Relatio...supporting
confidence: 92%
See 1 more Smart Citation
“…According to the findings of this study, social media influencer marketing plays a significant role in building brand awareness for any organization (β = 0.520, t = 5.150, p < 0.001). This is consistent with previous studies that have also found social media influencer marketing to be an effective way to increase brand awareness (Kwiatek et al, 2021). However, Vrontis et al…”
Section: H3: Social Media Influencer Marketing Has a Positive Relatio...supporting
confidence: 92%
“…This is consistent with previous studies, such as Ye et al (2021), which have shown that social media influencer marketing supports the primary objective of increasing revenue for a company by influencing customers to buy specific brand's products. Kwiatek et al (2021) concluded that the credibility of social media influencers is critical for the success of a business, which further emphasizes the importance of social media influencer marketing in driving purchasing decisions. Taking into consideration the results of this study (t = 5.150, β = 0.520, p < 0.001), it can also be concluded that social media influencer marketing is one of the most cost-effective ways to increase the likelihood of a consumer making a purchase.…”
Section: H1: Social Media Influencer Marketing Has a Positive Relatio...mentioning
confidence: 99%
“…Their primary duty is to represent and recommend brands to their followers, so influencing customer perceptions and consumers' purchasing decisions. 31 The disadvantage of this type of sanctioned information exchange is that customers are exposed to 'filtered' information. 32 This exposure raises the possibility of false information spreading on the social media site.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thanks to them, communication with consumers is much faster and more efficient. However, in order to convey the message even more effectively to the target market (about the value of brands), companies hire social media influencers, who are considered modern opinion makers in the digital environment [20].…”
Section: Travel Influencer Marketingmentioning
confidence: 99%